The level of depersonalization/derealization disorder (D.D.D) among refugees: A descriptive study of Syrian refugees in Mecca city in 2023 through some of demographic variables - Bin Hasan, Mohammad Ali (Journal of Educational and Psychological Sciences, 2023)
The study aimed to determine the level of depersonalization/derealization disorder and their relationship to some variables among a sample of Syrian refugees in Mecca city. The study sample consisted of 377 refugees, male and female, with different education levels, and traumatic experiences. They were selected by the Purposive Sample method, and to achieve the purposes of the study, The descriptive method was followed, using the D.D.D scale prepared by Omar (2018), which the researcher developed to suit the study sample. The validity and reliability of the scale was verified. To achieve the purpose of the study, the means, normative deviations, T-test have been used. The main results of the study were as follows: There is an average level of D.D.D in the study sample. The study also found statistically significant differences in the level of D.D.D (the only depersonalization factor) among refugees related to the gender variable in favor of females. There are also statistically significant differences in the levels of D.D.D in the refugee sample related to educational level, and traumatic experience in favor of High school qualification or lower. In the traumatic experience, the results of the Scheffe test for D.D.D showed that: the differences were in favor of the category of those who (were exposed to trauma before the asylum journey) compared to those who (did not experience refugee trauma), and in favor of the category of those who (were exposed to trauma during the asylum journey) compared to those who (exposure to trauma in the host country) And the category of those who (They did not experience refugee trauma). The study recommended the following: Establishing treatment programs by the Ministry of Health to reduce the level of D.D.D, and increasing attention to psychological care for refugees by providing a hotline to provide psychological support.
Keywords: Dissociation disorders; Depersonalization Derealization Disorder; Traumatic war Experiences; Syrian refugees